Conservation value of timber quality versus associated non-timber quality stands for understory diversity in Nothofagus forests - Lencinas, María Vanessa; Martínez Pastur, Guillermo José; Rivero, Paola; Busso, Carlos Alberto (Biodiversity and Conservation)
Conservation strategies of forested landscapes must consider biodiversity of the included site types, i.e. timber-quality forests and associated non-timber-quality stands. The objectives were to characterize forest overstory structure in timber-quality versus associated non-timber-quality stands; and to compare their understory communities. Six forest types were sampled in Nothofagus forests of Tierra del Fuego (Argentina): two timber-quality N. pumilio forests, and four associated non-timber-quality stands (edge, N. antarctica, wetlands and streamside forests). Overstory structure and understory vegetation (species richness, frequencies, cover and biomass) were characterized during spring and summer seasons. Analysis of variance and multivariates were carried out. Overstory structure differed across the site types, with higher tree size, canopy closure and tree volume in timber-quality stands. Fifty-one understory plant species were observed, but understory variables varied with site types, especially wetlands (highest native and exotic richness, cover and biomass, and 25% of exclusive species). Site types were grouped in three: N. antarctica stands, streamside stands and the other N. pumilio forests according to multivariate analysis. Forty three percent of plants were distributed in all site types, and all timber-quality forest understory species were present in some associated non-timber-quality stands. Timber-quality N. pumilio forests have a marginal value for understory conservation compared to associated non-timber-quality stands, because these last include all the plants observed in timber-quality forests and also possess many exclusive species. Therefore, protection of associated non-timber-quality stands during forest management planning could increase understory conservation at landscape level, and these could be better reserves of understory diversity than retentions of timber-quality stands. Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral ...